Digital postcompensation using volterra series transfer function - Guiomar, Fernando Pedro
We propose a noniterative digital backward propagation technique, based on an inverse modified Volterra series transfer function to postcompensate transmission linear and nonlinear impairments in the presence of optical noise. Using a single-channel 40-Gb/s nonreturn-to-zero quadrature phase-shift-keying optical signal propagated over 20 x 80 km of standard single-mode fiber, and performing digital postcompensation around the Nyquist rate, our compensation algorithm is able to surpass the maximum accuracy obtained with a symmetric split-step Fourier method, enabling us to increase the nonlinear tolerance by approximately 2 dB.